Pengaruh Electronic Word Of Mouth, Brand Image, Dan Kualitas Produk Terhadap Minat Beli Smartphone Merek Iphone Pada Generasi Y Dan Generasi Z Di Kota Bekasi - Muhammad Fahriansyah; Dewi Sri Woelandari Pantjolo; Bayu Seno Pitoyo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The research aims to empirically test the influence of electronic word of mouth, brand image, and product quality on interest in purchasing iPhone brand smartphone among generation Y and generation Z in Bekasi City. The sample for this research is generation Y and generation Z in Bekasi City who have an interest in buying iPhone brand smartphone. The sample was carried out using a non-probability sampling method, namely convenience sampling. Data collection was carried out using a questionnaire distributed via Goggle Form to 200 respondents. The analysis in this research uses Multiple Linear Regression Analysis, with t test hypothesis testing. The results of this research show that in the partial t test electronic word of mouth has no significant effect on purchase interest, brand image has a significant positive effect on purchase interest, and product quality has a significant positive effect on purchase interest. The results of the f test show that the variables electronic word of mouth, brand image, and product quality simultaneously influence the interest in buying iPhone brand smartphone among generation Y and generation Z in Bekasi City.